Immunologic Profiling of the Atlantic Salmon Gill by Single Nuclei Transcriptomics - West, Alexander C.; Mizoro, Yasutaka; Wood, Shona H.; Ince, Louise M.; Iversen, Marianne; Jørgensen, Even H.; Nome, Torfinn; Sandve, Simen Rød; Martin, Samuel A. M.; Loudon, Andrew S. I.; Hazlerigg, David G. (Frontiers in Immunology, 2021)
Anadromous salmonids begin life adapted to the freshwater environments of their natal streams before a developmental transition, known as smoltification, transforms them into marine-adapted fish. In the wild, smoltification is a photoperiod-regulated process, involving radical remodeling of gill function to cope with the profound osmotic and immunological challenges of seawater (SW) migration. While prior work has highlighted the role of specialized “mitochondrion-rich” cells (MRCs) and accessory cells (ACs) in delivering this phenotype, recent RNA profiling experiments suggest that remodeling is far more extensive than previously appreciated. Here, we use single-nuclei RNAseq to characterize the extent of cytological changes in the gill of Atlantic salmon during smoltification and SW transfer. We identify 20 distinct cell clusters, including known, but also novel gill cell types. These data allow us to isolate cluster-specific, smoltification-associated changes in gene expression and to describe how the cellular make-up of the gill changes through smoltification. As expected, we noted an increase in the proportion of seawater mitochondrion-rich cells, however, we also identify previously unknown reduction of several immune-related cell types. Overall, our results provide fresh detail of the cellular complexity in the gill and suggest that smoltification triggers unexpected immune reprogramming.